Empowering Rural Communities in Papua: Exploring Village Fund Management Socialization in Tablasupa, Jayapura - Ida Ayu Purba Riani; Marsi Adi Purwadi; Transna Putra Urip (Journal of Interdisciplinary Socio-Economic and Community Study, 2023)
This study investigates the effectiveness of training and socialization on village fund management in Tablasupa Village, Jayapura Regency, and its impact on participants' understanding of village fund management concepts and regulations. The uniqueness of Tablasupa Village as a case study lies in its rural setting and distinct socio-economic characteristics. By focusing on Tablasupa Village, this research presents a localized perspective on village fund management, emphasizing the need for tailored approaches that consider the specific needs and dynamics of rural areas. Prior to the training, participants had limited knowledge regarding key areas such as the definition of RPJMK (Regional Medium-Term Development Plan), the Village Law, types of village income, reporting of activity/program results, and accountability. However, after the training and discussions, participants showed significant improvement in their ability to answer questions correctly, indicating the effectiveness of the training. The study suggests that the training has practical implications in enhancing participants' understanding of financial management practices and empowering rural communities. However, it is important to consider the limitations of the study, such as its narrow focus on Tablasupa Village and the constraints of time and resources. Therefore, future research should encompass a larger sample size and explore multiple locations to obtain a more comprehensive understanding of village fund management in a broader context.